Religião, homossexualidade e poder: tensões nas Conferências de Lambeth e seus reflexos na Igreja Episcopal Anglicana do Brasil - Rodrigues, Silvia Geruza Fernandes (2020)
The main objective of this thesis was to analyze the Anglican Church documents issued at the Lambeth Conferences 1978 to 2008 on the sections relating to human sexuality and their reception in the Anglican Churches, especially in the Episcopal Anglican Church of Brazil. This work methodology work consisted of a bibliographic and documentary research. Michel Foucault’s concepts of religion domination of one’s sexuality as of a form of power and Pierre Bourdieu’s symbolic exchanges of power were fundamental theories for the analysis of the documents. We collected documents issued at the Lambeth Conferences on the websites of the Anglican Church and Anglican Episcopal Church of Brazil. We also conducted interviews with relevant leaders in the Episcopal Anglican Church of Brazil to have a more dynamic and live perspective on the entire process. The analysis pointed to a coalition of Conservatives from the Global North with Anglican Church leaders in the Global South in reaction to accepting openness to new scientific and medical discoveries about homosexuality, with a power play to reinstate orthodoxy and conservatism. Decolonialism has also contributed to the negative reception of Lambeth's resolutions, especially as regards to homosexuality, a sensitive and neuralgic issue in most churches in the Global South